Rural infrastructure development in the context of seasonal employment in agriculture of the Russian Federation - R. T. Kazaryan (Аграрная наука Евро-Северо-Востока)
The article examines the little-studied issue of seasonal employment in the agricultural economy as a vector of the employment category, the importance of which increases every year. In this regard, the purpose of the study is to develop proposals for improving state regulation of social protection issues for seasonal workers in agriculture. The long-overdue issues of regulating the labor relations of Russian agricultural producers with workers employed for seasonal work in terms of social guarantees require timely solutions. Also on the agenda are the acute problems of providing basic living conditions for the employees involved, especially with regard to housing conditions, transport and telecommunications infrastructure. As of the end of 2022, only 72 % of rural settlements have paved roads connected to the public road network, and the proportion of households in rural settlements with Internet access amounted to 81.2 %. The scientific novelty of the research consists in the development of specific measures of state participation in the development of basic rural infrastructure and the creation of favorable living conditions for seasonal workers in agricultural production. In particular, measures are proposed to stimulate the involvement of seasonal workers with the prospect of improving housing conditions. The use of the mechanism of concession agreements in terms of the development of transport infrastructure and the application of proven foreign practices in the development of telecommunications infrastructure, taking into account the consolidation at the legislative level, will allow the most effective use of the workforce of seasonal workers in the agricultural sector.